2015
DOI: 10.1002/2015gl063306
|View full text |Cite
|
Sign up to set email alerts
|

Causes and impacts of the 2014 warm anomaly in the NE Pacific

Abstract: Strongly positive temperature anomalies developed in the NE Pacific Ocean during the boreal winter of 2013–2014. Based on a mixed layer temperature budget, these anomalies were caused by lower than normal rates of the loss of heat from the ocean to the atmosphere and of relatively weak cold advection in the upper ocean. Both of these mechanisms can be attributed to an unusually strong and persistent weather pattern featuring much higher than normal sea level pressure over the waters of interest. This anomaly w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

33
892
2
16

Year Published

2015
2015
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 987 publications
(1,024 citation statements)
references
References 12 publications
33
892
2
16
Order By: Relevance
“…In our correlation analysis, we find that cool central northeast Pacific SSTs are concurrent with low SLPs in the same general region (SI Appendix, Fig. S8 B and F), consistent with Bond et al (36).…”
Section: Physical Mechanism For the Sst/slp Relationships With Us Mdasupporting
confidence: 77%
See 2 more Smart Citations
“…In our correlation analysis, we find that cool central northeast Pacific SSTs are concurrent with low SLPs in the same general region (SI Appendix, Fig. S8 B and F), consistent with Bond et al (36).…”
Section: Physical Mechanism For the Sst/slp Relationships With Us Mdasupporting
confidence: 77%
“…1B, which we use to predict summertime ozone in the eastern United States, also correlate strongly with the SST EOF2 time series (r = 0.84). In a case study, Bond et al (36) demonstrated that the SST warm anomaly during the winter of 2013-2014 was caused by anomalously high SLPs in that region, which suppressed the loss of heat from ocean to atmosphere and decreased cold advection in the upper ocean. In our correlation analysis, we find that cool central northeast Pacific SSTs are concurrent with low SLPs in the same general region (SI Appendix, Fig.…”
Section: Physical Mechanism For the Sst/slp Relationships With Us Mdamentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies link the increasing variance of the NPO-the atmospheric driver of the NPGO-to greenhouse forcing (29). Consistent with this view, in the winter of 2013-2014, the NPO activity reached a record high, causing the warmest SSTa anomalies ever recorded in the northeast Pacific (30). These SSTa anomalies exhibit the same spatial pattern as the NPGO (31), suggesting that extremes in physical conditions linked to salmon survival rates may become more frequent in future decades.…”
Section: Discussionsupporting
confidence: 48%
“…To protect public health, DA in shellfish has been monitored along the US West Coast since 1991 (19). These records are now long enough to investigate DA regulation at the temporal-spatial scales associated with NE Pacific climate events that have occurred in recent decades, such as El Niño events, PDO transitions, and the 2013-2015 NE Pacific Warm Anomaly (20,21).…”
mentioning
confidence: 99%